Condições de trabalho e saúde psíquica dos operários da construção civil - Clara Pires do Rêgo Lobão Amorim Leite (2012)
Considering that the construction sector is in the cycle of economic growth, and at the same time it faces management problems, as well as difficulty to attract labor force, this research have the goal to explore the relations between labor conditions and construction worker´s mental health. We started from psychosociological assumptions, among them include the structuring role of the work, and the need to understand the phenomenon at its individual, social and occupational manifests. Labor conditions and mental health phenomenons were understood in their theoretical perspective, which considers the multidimensional character of the subject. In the field of research, 236 workers from two constructions companies in Belo Horizonte participated. They answered individually the questionnaires about labor conditions, moderate mental disorders, self-esteem and affective welfare at work. It was realized analysis of variance among other statistics tests in accordance to the level of measures of the used indicators to explore if the work conditions varies with the construction workers mental health. The results corroborate that the labor conditions have an influence on construction workers mental health, since the exhausting work, the absence of autonomy, the reduced dialogue between workers and their superiors, as well as the absence of recognition of the value of their work contributes to the low self-esteem verified at this professional category, increased by the negative image of the construction work on the society. The team work, the sense of competence, the identification to activity, the sense of autonomy to define their tasks, contributes to the sense of self-efficacy and positive affections from these workers. The study shows that the kind of activity as well as the management style of the company is important to configure labor conditions and influencers to these professionals´ mental health. It also points to the need of investment on the development of interpersonal capacity, especially from the managers. The results can be largely used on social interventions to improve work conditions and construction workers´ mental health , under a psychological perspective.